Reconstruction of intestinal transit video-assisted after a Hartmann operation - Acevedo, Carlos; Caraballo, Mónica; Mandirola, Fernando; Crestanello, Francisco (Cirugía del Uruguay, 1998)
Rebuíldíng of transít after Hartmann's operatíon is a low mortalíty procedure, but wíth a no contemptíble morbílíty. Laparoscopíc approach of thís procedure show sorne advantages in front of tradítíonal approach. A case of vídeo assísted rebuíldíng of intestinal transít after Hartmann's operatíons is presented, wíth good postoperatory evolutíon.